Specific cutting energy analysis of turning Ti -6Al-4V under dry, wet and cryogenic conditions - Khan, Muhammad Ali; Jaffrey, Syed Husain Imran; Baqai, Aamer Ahmed; Khan, Mushtaq (Cranfield University, 2022)
Energy consumption of a manufacturing system represents its sustainability and efficiency. Sustainable manufacturing processes increase the productivity by improving the input to output ratio. Machining of hard to cut alloys demands higher energy input to overcome their high strength. The energy requirement also elevates with increasing speed which becomes the limiting factor. In the present study the specific cutting energy analysis of aerospace alloy Ti -6Al-4V was carried out at different cutting speeds. Different machining environment s including wet and cryogenic media were employed in addition to dry cutting for comprehensive analysis. It was found that cryogenic conditions reduced 8% and 11 % SCE in comparison with dry and wet conditions respectively. Analysis of variance highlighted contribution ratio of cutting speed and cutting condition as 51.87% and 46.98 %, respectively.
11th International Conference on Through-life Engineering Services - TESConf 2022, 8-9 November 2022, Cranfield UK
Keywords: Ti-6Al-4V; Cryogenic machining; Specific cutting energy; Analysis of variance